Radiation dose aspects and establishment of diagnostic reference levels for 90Y radioembolisation during angiographic procedure. (1st September 2022) - Opitz, Marcel; Zensen, Sebastian; Ludwig, Johannes Maximilian; Weber, Manuel; Alatzides, Georgios; Seifert, Robert; Grüneisen, Johannes; Theysohn, Jens Matthias; Bos, Denise; Schaarschmidt, Benedikt Michael
Abstract: 90 Y radioembolisation (RE) is an angiographic procedure used in patients with both primary and secondary hepatic malignancies. Local tumour control can be achieved by short range tumour irradiation by the regional intra-arterial administration of glass or resin microspheres loaded with 90yttrium that accumulate in the tumorous tissue. The aim of this study was to investigate the radiation exposure of RE and to establish a local diagnostic reference level (DRL). In this retrospective study, dose data from 397 procedures in 306 patients (mean age 67.4 ± 10.6 years, 82 female) who underwent RE between 06/2017 and 01/2022 using one of two different angiography systems were analysed. DRL was set as the 75th percentile of the dose distribution. In the overall population, dose area product (DAP) (median (interquartile range, IQR)) was 26 Gy cm 2 (IQR 12–50) with a median fluoroscopy time (FT) of 4.5 min (IQR 2.9–8.0). FT and DAP increased significantly with the number of infusion positions (median, IQR): one position 23 Gy cm 2 (12–46), two positions 33 Gy cm 2 (14–60), three positions 50 Gy cm 2 (24–82) ( p < 0.0001). Local DRL is 47 Gy cm 2 for RE and 111 Gy cm 2 for RE with additional embolisation. Radiation exposure and FT are significantly higher with increasing number of infusion positions as well as additional embolisation. Our established DRLs for RE may serve as a benchmark for dose optimisation.